Komunikasi Politik dan Retorika Debat antara Imam Syafi'i dan Harun al-Rasyid - Suhaimi Suhaimi (Buletin Al-Turas, 2007)
Political communication is communication activity that has political influence whether potential or actual to handle the people in conflict. While the political rhetoric defined as two ways communication that each of them realizes to influence the view of each other by reciprocal act.The debate that happened in Baghdad between Harun al-Rasyid Caliph and Imam Syafii who accused coup d'etat movement in communication context above is juridical, Imam Syafii s rhetoric message isforensic (Judicial) to show that he was success and not guilty.